Low cost bio-sorbent for the removal of phenolic compounds from olive mill wastewater - Mandi L.; Achak M.; Hafidi A.; Ouazzani N. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
The adsorption of phenolic compounds from olive mill wastewater (OMW) has been investigated as a function of adsorbent dose, pH and contact time. The results showed that the increase in the banana peel dosage from 10 to 30 g/L significantly increased the phenolic compound adsorption rates from 60 to 88 percent. Increase in the pH above neutrality resulted in the increase in the phenolic compound adsorption capacity. The adsorption process was fast, and it reached equilibrium in 3h contact time. The equilibrium process was described well by the Langmuir and Freundlich isotherm models with maximum sorption capacity of 688.9 mg/g of phenolic compounds on banana peel at 30°C. Banana peel, an inexpensive and easily available material, can be an alternative to more costly adsorbents used for the removal of phenolic compounds from olive mill wastewater (OMW).
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)